China's hold on the lithium-ion battery supply chain: Prospects for competitive growth and sovereign control - Tim Greitemeier; Achim Kampker; Jens Tübke; Simon Lux (Journal of Power Sources Advances)
Battery production for electric vehicles (EVs) necessitates a supply chain capable of supporting the exploitation of a variety of raw materials. Lithium, nickel, manganese, and cobalt are of particular significance for the dominant lithium-ion battery (LIB) technology, primarily relying on lithium iron phosphate (LFP) and lithium nickel manganese cobalt oxide (NMC) cathodes. Geographically, the global supply is heavily reliant on China with competition expected to intensify. In light of this, the questions of how global competition manifests at the company level and whether regions capture their share of the supply chain through domestic companies remain unanswered. These are addressed by analyzing the companies behind each supply chain sector and the respective raw materials. The results demonstrate that China, Europe, and the United States of America (USA) exhibit the most pronounced ownership across the supply chain, acquiring the largest foreign shares in the mining sector. Overall, China leads in a total of eleven out of the 12 investigated sectors, with its peak for LFP production at above 98 %. This preeminence, coupled with the substantial output of South Korea, Europe, and Japan in NMC production, the latter represents a viable target for mitigating supply chain vulnerabilities and attaining greater growth and sovereignty.